Thermoelectric conversion material, thermoelectric element, thermometer, and sensor
By using a magnetic alloy containing Fe, the first metal element and the second metal element in the thermoelectric conversion material, the existing materials have been solved, and a thermoelectric conversion material with high coercive force and good magnetic resistance is achieved.
Patent Information
- Application Number
- JP2023164169
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
When existing thermoelectric conversion materials are applied with magnetic fields, their power generation and thermal detection characteristics are easily affected, and coercive forces are limited and it is difficult to improve magnetic resistance.
A magnetic alloy containing iron (Fe), a first metal element and a second metal element is used, the second metal element has a monomer center symmetric cubic crystal structure and an atomic radius greater than 132 picometers, and a thermoelectric conversion material with an abnormal Nunn effect is demonstrated.
The magnetic resistance and coercive force of thermoelectric conversion materials are improved, so as to maintain good power generation and thermal detection performance under external magnetic field conditions.
Smart Images

Figure 2025054928000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a thermoelectric conversion material, a thermoelectric conversion element, a thermometer, and a sensor.
Background Art
[0002] Conventionally, substances showing an abnormal Nernst effect have been known.
[0003] For example, Patent Document 1 describes a thermoelectric conversion element made of a substance showing an abnormal Nernst effect. As substances showing an abnormal Nernst effect, a first substance, a second substance, a third substance, a fourth substance, and a fifth substance are described. The first substance is a substance having a stoichiometric composition represented by the composition formula Fe3X, where X is a typical element or a transition element. The second substance is a substance having an off-stoichiometric composition in which the composition ratio of Fe and X deviates from that of the first substance. The third substance is a substance obtained by substituting part of the Fe sites of the first substance or part of the Fe sites of the second substance with a typical metal element or a transition element other than X. The fourth substance has a composition formula Fe3M1 1-x M2 x (0 < x < 1), where M1 and M2 are different typical elements. The fifth substance is a substance obtained by substituting part of the Fe sites of the first substance with a transition element other than X and substituting part of the X sites with a typical metal element other than X. According to Patent Document 1, such substances are described as being inexpensive.
[0004] Patent Document 1 describes the coercive force of Y 0.05 Fe 2.95 Ga (about 20 Oe), the coercive force of Tb 0.05 Fe 2.95 Ga (about 40 Oe), the coercive force of a needle-shaped sample of Fe3Ga (about 10 Oe), the coercive force of a needle-shaped sample of Fe3Ga 0.8 B 0.2 (about 35 Oe), the coercive force of a needle-shaped sample of Fe 2.9 Pt 0.1 Ga 0.9 Ge 0.1 (about 8 Oe). In addition, it is described that the coercive force of a thin film sample of Fe3Ga with a thickness of 50 nm is about 40 Oe. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2020 / 218613 Summary of the Invention [Problem to be solved by the invention]
[0006] As the Internet of Things (IoT) society and digital transformation (DX) progress, there is a growing need for heat monitoring in technical fields such as monitoring heat generation from machines and physical condition. In addition, from the perspective of protecting the global environment, it is important to suppress unnecessary heat generation and increase energy utilization efficiency, and there are high expectations for the advancement of systems that measure heat to optimize operations in various technical fields such as batteries, heat exchangers, and motors for electric vehicles (EVs).
[0007] Thermoelectric materials exhibiting the anomalous Nernst effect are promising as a technology that meets such expectations. Coercive force is known as an index of the magnetic resistance of a magnetic material. When an external magnetic field exceeding the coercive force of the thermoelectric material is applied to a thermoelectric conversion element having a thermoelectric conversion material, the characteristics of the thermoelectric conversion element, such as the power generation characteristics and heat detection characteristics, may be deteriorated. For this reason, it is important to increase the coercive force of the thermoelectric conversion material, for example, in order to make the characteristics of the thermoelectric conversion element less susceptible to the influence of the surrounding magnetic field. On the other hand, in the thermoelectric conversion element described in Patent Document 1, the coercive force of the material exhibiting the anomalous Nernst effect is not high, and in particular, the coercive force of the material containing Fe and multiple types of metal elements other than Fe is only about 40 Oe.
[0008] In view of the above circumstances, the present invention provides a thermoelectric conversion material that contains Fe and is advantageous in terms of increasing magnetic resistance. [Means for solving the problem]
[0009] The present invention relates to A magnetic alloy containing Fe, a first metallic element, and a second metallic element, the first metal element and the second metal element are different metal elements other than Fe, the second metal element is a metal element having a body-centered cubic lattice structure by itself and an atomic radius of 132 picometers or more; exhibits the anomalous Nernst effect, A thermoelectric conversion material is provided.
[0010] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: A thermometer including the above thermoelectric conversion element is provided.
[0011] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: The thermoelectric conversion element is provided. Detecting heat generated by storage batteries, A sensor is provided. Effect of the Invention
[0012] The above-mentioned thermoelectric conversion material is advantageous from the viewpoint of increasing the antimagnetic property while containing Fe. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a plan view showing an example of an embodiment of a thermoelectric conversion material. [Diagram 2] FIG. 2 is a cross-sectional view of the thermoelectric conversion material taken along line II-II shown in FIG. [Diagram 3] FIG. 3 is a graph showing the relationship between the magnetization of a thermoelectric conversion material and an external magnetic field. [Figure 4] FIG. 4 is a plan view showing an example of an embodiment of a thermoelectric conversion element. [Diagram 5] FIG. 5 is a cross-sectional view of the thermoelectric conversion element taken along line VV shown in FIG. [Figure 6] FIG. 6 is a diagram illustrating an example of an embodiment of a thermoelectric conversion device. [Figure 7]FIG. 7 is a transmission electron microscope (TEM) photograph of the thermoelectric conversion material according to Example 3. [Figure 8] FIG. 8 is a TEM photograph of the thermoelectric conversion material according to Comparative Example 1. [Figure 9] FIG. 9 is a diagram showing a schematic diagram of a method for measuring the internal stress of a thermoelectric conversion material. [Figure 10] FIG. 10 is a graph showing an X-ray diffraction (XRD) pattern of the thermoelectric conversion material according to Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that the following description is for illustrative purposes only and the present invention is not limited to the following embodiment. In the accompanying drawings, the X-axis, the Y-axis, and the Z-axis are mutually orthogonal.
[0015] 1 and 2 show a thermoelectric conversion material 1. The thermoelectric conversion material 1 includes a magnetic alloy containing Fe, a first metal element, and a second metal element. The first metal element and the second metal element are different metal elements other than Fe. The second metal element is a metal element that has a body-centered cubic lattice structure by itself and has an atomic radius of 132 picometers or more. The thermoelectric conversion material 1 exhibits the anomalous Nernst effect. For this reason, for example, when a heat flow is generated in the thermoelectric conversion material 1, an electromotive force is generated in a direction (Y-axis direction) perpendicular to the direction of the heat flow (Z-axis direction) and the magnetization direction (X-axis direction) of the thermoelectric conversion material 1.
[0016] In the thermoelectric conversion material 1, the magnetic alloy contains the second metal element, so that the thermoelectric conversion material 1 is likely to have a high coercive force. Therefore, the thermoelectric conversion material 1 is likely to exhibit high magnetic resistance while containing Fe. For example, the thermoelectric conversion material 1 is likely to have a higher coercive force than a thermoelectric conversion material that does not contain the second metal element, contains a magnetic alloy containing Fe and the first metal element, and has the same dimensions as the thermoelectric conversion material 1. The reason why the magnetic alloy contained in the thermoelectric conversion material 1 is likely to have a high coercive force due to the inclusion of the second metal element is not clear. However, the inventors believe that the grain size of the magnetic alloy is easily adjusted to a desired range by the Fe-containing magnetic alloy containing a metal element that has a body-centered cubic lattice structure by itself and has an atomic radius of 132 picometers or more, which may contribute to the coercive force of the thermoelectric conversion material 1. If the grain size of the magnetic material is close to the single magnetic domain size, the coercive force of the magnetic material is likely to be high.
[0017] The contents of Fe, the first metal element, and the second metal element in the magnetic alloy contained in the thermoelectric conversion material 1 are not limited to specific values. For example, the content a of Fe based on the amount of substance, the content b of the first metal element based on the amount of substance, and the content c of the second metal element based on the amount of substance in the magnetic alloy satisfy the conditions of 0.1≦b / (a+b)≦0.33 and 0.01≦c / (a+b+c)≦0.1. In this case, the thermoelectric conversion material 1 is more likely to have a high coercive force.
[0018] In the magnetic alloy, the following condition may be satisfied: 0.12≦b / (a+b)≦0.32, 0.13≦b / (a+b)≦0.31, 0.14≦b / (a+b)≦0.30, 0.15≦b / (a+b)≦0.28, 0.15≦b / (a+b)≦0.26, or 0.15≦b / (a+b)≦0.24.
[0019] In the magnetic alloy, the following condition may be satisfied: 0.01≦c / (a+b+c)≦0.09, 0.01≦c / (a+b+c)≦0.08, 0.01≦c / (a+b+c)≦0.07, 0.01≦c / (a+b+c)≦0.06, 0.01≦c / (a+b+c)≦0.05, or 0.02≦c / (a+b+c)≦0.04.
[0020] The composition of the magnetic alloy is not limited to a specific composition as long as it contains Fe, a first metal element, and a second metal element. a D b E c In this composition, D is a first metal element, and E is a second metal element. In this composition, a, b, and c are rational numbers that satisfy the condition a>b>c>0. When the magnetic alloy has such a composition, the thermoelectric conversion material 1 is more likely to have a high coercive force. The magnetic alloy may contain elements other than Fe, the first metal element, and the second metal element. In this composition, the relationship between a, b, and c may satisfy the same relationship as the relationship between the content a of Fe based on the amount of substance, the content b of the first metal element based on the amount of substance, and the content c of the second metal element based on the amount of substance.
[0021] The crystal structure of the magnetic alloy is not limited to a specific crystal structure. The magnetic alloy has, for example, a body-centered cubic lattice structure. In this case, the thermoelectric conversion material 1 is more likely to have a high coercive force. The crystal structure of the magnetic alloy can be determined, for example, based on the X-ray diffraction (XRD) pattern of the magnetic alloy.
[0022] The first metal element contained in the magnetic alloy is not limited to a specific metal element as long as it is a metal element different from Fe and the second metal element. The first metal element includes, for example, at least one selected from the group consisting of Al, Si, Zn, Ga, Ge, Cd, In, and Sn. In this case, the thermoelectric conversion material 1 is likely to exhibit the desired thermoelectric conversion characteristics.
[0023] The second metal element contained in the magnetic alloy is not limited to a specific metal element, as long as it has a body-centered cubic lattice structure by itself and has an atomic radius of 132 picometers or more. The second metal element may include, for example, at least one selected from the group consisting of Ta, Nb, W, Mo, and V. The second metal element may include at least one selected from the group consisting of Ta, Nb, and W. In this case, the thermoelectric conversion material 1 is more likely to have a high coercive force.
[0024] The magnetic alloy is, for example, polycrystalline, which makes it easier for the thermoelectric conversion material 1 to exhibit desired thermoelectric conversion characteristics.
[0025] The shape of the thermoelectric conversion material 1 is not limited to a specific shape, and the dimensions of the thermoelectric conversion material 1 are not limited to a specific value. As shown in Fig. 2, the thermoelectric conversion material 1 has, for example, a predetermined thickness d. The thickness d is, for example, the dimension of the thermoelectric conversion material 1 in the Z-axis direction. The thermoelectric conversion material 1 has a thickness of, for example, 200 nm or less. In this case, the thermoelectric conversion material 1 is more likely to have a high coercive force.
[0026] The thickness d of the thermoelectric conversion material 1 is desirably 180 nm or less, more desirably 150 nm or less, even more desirably 120 nm or less, particularly desirably 100 nm or less, and especially desirably 50 nm or less.
[0027] The thickness d of the thermoelectric conversion material 1 is, for example, 5 nm or more. In this case, the thermoelectric conversion material 1 is likely to have a desired electrical resistance, and noise is unlikely to occur in a thermoelectric conversion element including the thermoelectric conversion material 1. The thickness d of the thermoelectric conversion material 1 is preferably 10 nm or more, and more preferably 15 nm or more.
[0028] 2, the thermoelectric conversion material 1 is in the form of, for example, a film. The internal stress σ x and the internal stress σ of the membrane in the second direction (Y-axis direction) perpendicular to the first direction and along the membrane's plane. y The relationship between is not limited to a specific relationship. For example, the internal stress σx and internal stress σ y Difference from |σ x -σ y is 50 MPa or more. In this case, the thermoelectric conversion material 1 is more likely to have a high coercive force.
[0029] FIG. 3 is a graph showing the relationship between the magnetization of a thermoelectric conversion material and an external magnetic field. In FIG. 3, the solid line graph shows the relationship between the magnetization of thermoelectric conversion material 1 in a first direction (X-axis direction) and an external magnetic field. The dashed line graph shows the relationship between the magnetization of thermoelectric conversion material 1 in a second direction (Y-axis direction) and an external magnetic field. As shown in FIG. 3, the magnetic properties of thermoelectric conversion material 1 may have large anisotropy in the second direction and the first direction. The difference |σ x -σ y When | is 50 MPa or more, the magnetic properties of the thermoelectric conversion material 1 are likely to have such anisotropy. By utilizing such anisotropy of the magnetic properties, it is possible to increase the coercive force of the thermoelectric conversion material 1. For example, when the thermoelectric conversion material 1 is magnetized in the first direction (X-axis direction), the coercive force of the thermoelectric conversion material 1 is likely to be high, and the magnetic resistance of the thermoelectric conversion material 1 is likely to be high.
[0030] In thermoelectric material 1, the difference |σ x -σ y | may be 50 MPa or more, 100 MPa or more, or 200 MPa or more. x -σ y The upper limit of | is not limited to a specific value. x -σ y is, for example, 1000 MPa or less. In this case, even if a bending load is applied to the thermoelectric conversion material 1 in the first direction, cracks are unlikely to occur in the thermoelectric conversion material 1.
[0031] Internal stress σ x may be a tensile stress or a compressive stress. xmay be included in any of the ranges determined by all combinations of a lower limit that is any one of −2000 MPa, −1000 MPa, −500 MPa, and −300 MPa and an upper limit that is any one of 1000 MPa, 500 MPa, 200 MPa, and 100 MPa.
[0032] Internal stress σ y may be a tensile stress or a compressive stress. y may be included in any of the ranges determined by all combinations of a lower limit that is any one of −2000 MPa, −1000 MPa, −500 MPa, and −300 MPa and an upper limit that is any one of 1000 MPa, 500 MPa, 200 MPa, and 100 MPa.
[0033] As shown in FIG. 1, the thermoelectric conversion material 1 is disposed on a substrate 2. The material of the substrate 2 is not limited to a specific material. The substrate 2 contains, for example, an organic material. In this case, it is easy to adjust the internal stress in the thermoelectric conversion material 1 to a desired state from the viewpoint of improving the coercive force. In addition, the substrate 2 contains, for example, an organic polymer as the organic material. Examples of the organic polymer are polyethylene terephthalate (PET), polyethylene naphthalate (PEN), acrylic resin (PMMA), polycarbonate (PC), polyimide (PI), or cycloolefin polymer (COP).
[0034] The thickness of the substrate 2 is not limited to a specific value, and is, for example, 10 to 250 μm.
[0035] The substrate 2 has, for example, flexibility. The substrate 2 has elasticity that allows the test specimen to be elastically deformed when, for example, a strip-shaped test specimen made from the substrate 2 is wound around a cylindrical mandrel having a diameter of 10 cm so that both ends in the longitudinal direction of the test specimen face in the same direction.
[0036] For example, a thermoelectric conversion element including the thermoelectric conversion material 1 can be provided. As shown in Fig. 4 and Fig. 5, in the thermoelectric conversion element 5, the thermoelectric conversion material 1 is, for example, in the form of a thin wire. According to such a configuration, for example, by providing magnetization in the width direction of the thin wire of the thermoelectric conversion material 1, when a temperature gradient occurs in the thickness direction (Z-axis direction) of the substrate 2, a thermoelectromotive force associated with the anomalous Nernst effect can be generated in the length direction of the thin wire. In this case, a thermoelectromotive force according to the length of the thin wire can be generated, and the thermoelectric conversion element 5 is likely to exhibit the desired thermoelectric conversion performance.
[0037] The width of the thin wires of the thermoelectric conversion material 1 is not limited to a specific value. The width of the thin wires is, for example, 500 μm or less. This allows the amount of material used for the thin wires to be reduced, making it easy to reduce the manufacturing costs of the thermoelectric conversion element 5. In addition, it is easy to arrange a large number of thin wires in the thermoelectric conversion element 5, making it easier for the thermoelectric conversion element 5 to exhibit the desired thermoelectric conversion performance. The width of the thin wires is, for example, 1 μm or more. This makes it difficult for breaks to occur in the thin wires, making it easy for the thermoelectric conversion element 5 to have high durability.
[0038] The width of the thin wires formed by the thermoelectric conversion material 1 may be included in any of the ranges determined by all combinations of a lower limit value of any one of 1 μm, 2 μm, 5 μm, 10 μm, 20 μm, and 30 μm and an upper limit value of any one of 500 μm, 400 μm, 300 μm, 200 μm, 100 μm, and 50 μm.
[0039] As shown in FIG. 4 and FIG. 5, in the thermoelectric conversion element 5, the thermoelectric conversion material 1 forms a plurality of thin wires, and these thin wires form the thermoelectric conversion section 10. The thermoelectric conversion element 5 has, for example, a meander pattern including the thermoelectric conversion material 1. With such a configuration, the total length of the thin wires formed by the thermoelectric conversion material 1 in the thermoelectric conversion element 5 tends to be large. The electromotive force generated in the length direction (Y-axis direction) of the thin wires due to the temperature gradient in the thickness direction (Z-axis direction) of the substrate 2 tends to be large as the total length of the thin wires including the thermoelectric conversion material 1 is large. For this reason, when the thermoelectric conversion element 5 has a meander pattern including the thermoelectric conversion material 1, the electromotive force generated in the thermoelectric conversion element 5 tends to be large.
[0040] As shown in Figs. 4 and 5, the thermoelectric conversion element 5 further includes, for example, wiring 30. The wiring 30 electrically connects the thermoelectric conversion materials 1 forming thin wires to each other. For example, the thermoelectric conversion materials 1 forming a plurality of thin wires are electrically connected in series by the wiring 30. The wiring 30 includes, for example, a plurality of wirings 3. The plurality of thin wires formed by the thermoelectric conversion material 1 and the plurality of wirings 3 are electrically connected in series. With this configuration, a large electromotive force is likely to be generated in the thermoelectric conversion element 5 even if the area of the surface on which the thermoelectric conversion section 10 and the wiring 30 are arranged is small.
[0041] The wiring 30 may be made of a single metal or an alloy.
[0042] The multiple fine wires and multiple wirings 3 of the thermoelectric conversion material 1 are arranged, for example, to form the meander pattern described above. This forms a conductive path 20. For example, one end and the other end of the conductive path 20 are connected to external wiring, so that the electromotive force generated in the thermoelectric conversion element 5 can be extracted to the outside. Alternatively, a voltage can be applied between one end and the other end of the conductive path 20 to generate a heat flow in the thickness direction of the substrate 2.
[0043] The thermoelectric conversion material 1 forming a plurality of thin wires is arranged, for example, at a predetermined interval in the X-axis direction and parallel to one another. The wiring 3 electrically connects, for example, one end of a thin wire formed by the thermoelectric conversion material 1 in the Y-axis direction to the other end in the Y-axis direction of a thin wire formed by another thermoelectric conversion material 1 adjacent to the thin wire.
[0044] The thickness of the wiring 3 is not limited to a specific value, and may be within any range determined by any combination of a lower limit of any one of 5 nm, 10 nm, 20 nm, 30 nm, and 50 nm and an upper limit of any one of 1000 nm, 750 nm, 500 nm, 400 nm, 300 nm, and 200 nm, for example.
[0045] The width of the wiring 3 is not limited to a specific value, and may be included in any of the ranges determined by all combinations of a lower limit of any one of 0.1 μm, 0.5 μm, 1 μm, 2 μm, 5 μm, 10 μm, 20 μm, and 30 μm and an upper limit of any one of 500 μm, 400 μm, 300 μm, 200 μm, 100 μm, and 50 μm.
[0046] An example of a method for manufacturing the thermoelectric conversion element 5 is shown. For example, a film of a precursor of the thermoelectric conversion unit 10 is formed on one main surface of the base material 2 by a method such as sputtering, chemical vapor deposition (CVD), pulsed laser deposition (PLD), ion plating, and plating. Next, for example, a photoresist is applied on the film, a photomask is placed on the film, exposure is performed, and then wet etching is performed. As a result, a plurality of thin wires of the precursor of the thermoelectric conversion unit 10 arranged at a predetermined interval are formed. Next, a film of a precursor of the wiring 3 is formed on one main surface of the base material 2 by a method such as sputtering, CVD, PLD, ion plating, and plating. Next, a photoresist is applied on the film of the precursor of the wiring 30, a photomask is placed on the film of the precursor of the wiring 30, exposure is performed, and then wet etching is performed. As a result, the wiring 30 is obtained, and the thin wires of the precursor of the thermoelectric conversion unit 10 are electrically connected to each other.
[0047] A predetermined heat treatment is performed as necessary. The ambient temperature of the substrate 2 and the precursor of the thermoelectric conversion section 10 during the heat treatment is, for example, 50°C or higher. This makes it easy to adjust the internal stress of the thermoelectric conversion material 1 to a desired state in terms of high coercive force. The ambient temperature of the substrate 2 and the precursor of the thermoelectric conversion section 10 during the heat treatment may be 100°C or higher, 150°C or higher, or 200°C or higher. The ambient temperature is, for example, 300°C or lower.
[0048] The time during which the ambient temperature of the substrate 2 is kept at 50° C. or higher in the heat treatment is not limited to a specific value, and is, for example, 10 minutes or more and 3 hours or less.
[0049] After the heat treatment, the precursor of the thermoelectric conversion section 10 is magnetized, and the thermoelectric conversion material 1 and the thermoelectric conversion section 10 are obtained.
[0050] The thermoelectric conversion element 5 may be provided together with, for example, an adhesive layer. In this case, the adhesive layer is in contact with the base material 2, and the base material 2 is disposed between the thermoelectric conversion section 10 and the adhesive layer in the thickness direction of the base material 2. This allows the adhesive layer to be pressed against an article, thereby attaching the thermoelectric conversion element 5 to the article.
[0051] The adhesive layer contains, for example, a rubber-based adhesive, an acrylic-based adhesive, a silicone-based adhesive, or a urethane-based adhesive. The thermoelectric conversion element 5 may be provided together with the adhesive layer and a release liner. In this case, the release liner covers the adhesive layer. The release liner is typically a film that can maintain the adhesive force of the adhesive layer when covering the adhesive layer and can be easily peeled off from the adhesive layer. The release liner is, for example, a film made of a polyester resin such as PET. The adhesive layer is exposed by peeling off the release liner, and the thermoelectric conversion element 5 can be attached to an article.
[0052] As shown in FIG. 6, for example, a thermoelectric conversion device 7 including a thermoelectric conversion element 5 can be provided. This thermoelectric conversion device 7 is, for example, a sensor that detects heat in an object. For example, when a temperature gradient occurs in the thickness direction of the base material 2, an electromotive force is generated in the Y-axis direction. The thermoelectric conversion device 7 can sense heat by processing an electric signal outputted to the outside of the thermoelectric conversion element 5 based on this electromotive force. The thermoelectric conversion device 7 further includes, for example, a signal processing device 6. In the signal processing device 6, the electric signal outputted to the outside of the thermoelectric conversion element 5 is processed.
[0053] The object for which the thermoelectric conversion device 7 detects heat is not limited to a specific object. The object may be a storage battery such as a lithium ion battery, a human body, or other objects. For example, the thermoelectric conversion device 7 is a sensor that detects heat generated in a storage battery. In this case, the thermoelectric conversion device 7 can detect the amount of heat generated or the internal temperature in the storage battery. This allows the deterioration state of the storage battery to be estimated. The thermoelectric conversion device 7 may also be used to adjust the temperature of the storage battery. This is expected to improve the range of electric vehicles (EVs), for example. A magnetic field may be generated around the storage battery due to an electric current. As described above, the thermoelectric conversion material 1 is likely to have a high coercive force, and therefore the thermoelectric conversion element 5 is likely to have a high magnetic resistance. Therefore, even if the object for which the thermoelectric conversion device 7 detects heat is a storage battery, the thermoelectric conversion element 5 is likely to exhibit high reliability.
[0054] The thermoelectric conversion device 7 may be configured as a thermometer. For example, the thermoelectric conversion device 7 may be used as a wearable thermometer. In this case, the deep body temperature can be measured from above the skin even when exposed to sunlight or taking a bath. This is expected to enable early detection of the risk of heat stroke and a sudden change in physical condition due to heat shock. As described above, the thermoelectric conversion material 1 tends to have a high coercive force, so that accurate measurement of body temperature can be possible even if a magnet approaches the thermoelectric conversion device 7 used as a wearable thermometer. The thermoelectric conversion device 7 may be configured as a device other than a sensor. EXAMPLES
[0055] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples. First, the evaluation methods used in the examples will be described.
[0056] <Example 1> A thin film having a thickness of 30 nm was formed on a 50 μm thick polyethylene terephthalate (PET) film by DC magnetron sputtering using a target material containing Fe, Ga, and Ta. In the DC magnetron sputtering, argon gas was supplied as a process gas at a pressure of 0.1 Pa. In the target material, the Fe content a, Ga content b, and Ta content c, based on the amount of substance, satisfied the relationship shown in Table 1.
[0057] Next, the temperature around the PET film was adjusted to 200° C. The lower film on which the thin film was formed was heat-treated for 30 minutes in an environment of 200° C. Thereafter, the thin film was magnetized in a specific direction parallel to the main surface of the PET film using an electromagnet having a central magnetic flux density of 0.5 T, thereby obtaining a thermoelectric conversion material according to Example 1.
[0058] <Example 2> A thermoelectric conversion material according to Example 2 was obtained in the same manner as in Example 1, except for the following points. In the target material, the Fe content a, Ga content b, and Ta content c, based on the amount of substance, were adjusted to satisfy the relationships shown in Table 1. The thickness of the thin film was adjusted to 25 nm by DC magnetron sputtering.
[0059] <Example 3> A thermoelectric conversion material according to Example 3 was obtained in the same manner as in Example 1, except for the following points. In the target material, the Fe content a, the Ga content b, and the Ta content c, based on the amount of substance, were adjusted so as to satisfy the relationships shown in Table 1.
[0060] <Example 4> A thermoelectric conversion material according to Example 4 was obtained in the same manner as in Example 1, except for the following points. In the target material, the Fe content a, Ga content b, and Ta content c, based on the amount of substance, were adjusted to satisfy the relationships shown in Table 2. The thickness of the thin film was adjusted to 100 nm by DC magnetron sputtering.
[0061] <Example 5> A thermoelectric conversion material according to Example 5 was obtained in the same manner as in Example 1, except for the following points. Instead of a target material containing Fe, Ga, and Ta, a target material containing Fe, Ga, and Nb was used. In the target material, the Fe content a, Ga content b, and Nb content c on a substance basis were adjusted to satisfy the relationships shown in Table 1.
[0062] <Example 6> A thermoelectric conversion material according to Example 6 was obtained in the same manner as in Example 1, except for the following points. Instead of a target material containing Fe, Ga, and Ta, a target material containing Fe, Ga, and W was used. In the target material, the Fe content a, Ga content b, and W content c, based on the amount of substance, were adjusted so as to satisfy the relationships shown in Table 1.
[0063] <Comparative Example 1> A thermoelectric conversion material according to Comparative Example 1 was obtained in the same manner as in Example 1, except for the following points. Instead of a target material containing Fe, Ga, and Ta, a target material containing Fe and Ga was used. In the target material, the Fe content a and the Ga content b on a substance basis were adjusted so as to satisfy the relationship shown in Table 1.
[0064] <Comparative Example 2> A thermoelectric conversion material according to Comparative Example 2 was obtained in the same manner as in Example 1, except for the following points. Instead of a target material containing Fe, Ga, and Ta, a target material containing Fe, Ga, and Cr was used. In the target material, the Fe content a, Ga content b, and Cr content c on a substance amount basis were adjusted so as to satisfy the relationships shown in Table 1.
[0065] <Comparative Example 3> A thermoelectric conversion material according to Comparative Example 3 was obtained in the same manner as in Example 1, except for the following points. Instead of a target material containing Fe, Ga, and Ta, a target material containing Fe, Ga, and Pt was used. In the target material, the Fe content a, Ga content b, and Pt content c on a substance amount basis were adjusted so as to satisfy the relationships shown in Table 1.
[0066] <Comparative Example 4> A thermoelectric conversion material according to Comparative Example 4 was obtained in the same manner as in Example 1, except for the following points. Instead of a target material containing Fe, Ga, and Ta, a target material containing Fe, Ga, and Zr was used. In the target material, the Fe content a, Ga content b, and Zr content c on a substance amount basis were adjusted so as to satisfy the relationships shown in Table 1.
[0067] <Comparative Example 5> A thermoelectric conversion material according to Comparative Example 5 was obtained in the same manner as in Example 1, except for the following points. A target material containing Fe and Ga was used instead of a target material containing Fe, Ga, and Ta. In the target material, the Fe content a and the Ga content b on a substance basis were adjusted to satisfy the relationship shown in Table 2. The thickness of the thin film was adjusted to 100 nm in DC magnetron sputtering.
[0068] [Anomalous Nernst effect] For the thermoelectric conversion materials according to each of the Examples and Comparative Examples, a temperature gradient was generated in the thickness direction of the PET film without the application of an external magnetic field. This confirmed that an electromotive force was generated in the plane of the thin film of the thermoelectric conversion material in a direction perpendicular to the magnetization of the thermoelectric conversion material. Therefore, it was confirmed that the thermoelectric conversion materials according to each of the Examples and Comparative Examples exhibited the anomalous Nernst effect.
[0069] [Magnetic properties] The magnetic properties of the thermoelectric conversion materials according to each Example and Comparative Example were measured using a physical property measuring device PPMS-versalab from Qantum Design. For this measurement, a measurement sample was prepared by cutting out a portion including the thermoelectric conversion material according to each Example and Comparative Example into a 2 mm square. In addition, a Vibration Sample Magnetrometer (VSM) was used in the measurement, and a magnetic field of ±500 [Oe] was swept parallel to the magnetization direction of the thermoelectric conversion material, and an M-H curve was obtained at a temperature of 300 K, taking into account the thickness of the thermoelectric conversion material and the area of the thermoelectric conversion material in the measurement sample. The coercive force of each thermoelectric conversion material was determined from the obtained M-H curve. The results are shown in Table 1 or Table 2.
[0070] [Grain size] Samples made from the thermoelectric conversion materials according to each of the Examples and Comparative Examples were observed with a transmission electron microscope TEM-2800 manufactured by JEOL Ltd. to obtain planar TEM photographs of each thermoelectric conversion material. These TEM photographs suggested that the thermoelectric conversion materials contained polycrystalline magnetic alloys. FIG. 7 is a TEM photograph of the thermoelectric conversion material according to Example 3, and FIG. 8 is a TEM photograph of the thermoelectric conversion material according to Comparative Example 1. The grain size of the thermoelectric conversion material according to Comparative Example 1 was 10 to 50 nm, and the grain size of the thermoelectric conversion material according to Example 3 was 10 to 70 nm. The average grain size of the thermoelectric conversion material according to Example 3 was larger than the grain size of the thermoelectric conversion material according to Comparative Example 1.
[0071] Internal Stress Using a Rigaku Corporation X-ray diffraction apparatus Smartlab, the sample was irradiated with Cu-Kα radiation from a 40 kV and 50 mA light source through a parallel beam optical system. 2 The internal stress σ of the thermoelectric conversion material according to each example and each comparative example is calculated based on the principle of the tilt method of the Ψ method. x and internal stress σ y The internal stress σ x is the internal stress in the magnetization direction of the thermoelectric material, and the internal stress σ ywas the internal stress in a direction parallel to the main surface of the PET film and perpendicular to the magnetization direction of the thermoelectric conversion material. The wavelength λ of the Cu-Kα radiation was 0.1541 nm. sin 2 The Ψ method is a method for determining the internal stress of a thin film from the dependence of the crystal lattice distortion of the polycrystalline thin film on the angle (Ψ). Using the above-mentioned X-ray diffraction device, the diffraction intensity was measured at 0.01° intervals in the range of 2θ = 75° to 85° by Θ / 2Θ scan measurement. The integration time at each measurement point was set to 100 seconds. The crystal lattice plane spacing d of the magnetic material at each measurement angle (Ψ) was calculated from the peak angle 2θ of the obtained X-ray diffraction and the wavelength λ of the X-ray irradiated from the light source, and the crystal lattice distortion ε was calculated from the crystal lattice plane spacing d according to the relationship of the following formulas (1) and (2). λ is the wavelength of the X-ray (Cu-Kα line) irradiated from the light source, and λ = 0.1541 nm. d0 is the lattice plane spacing of the crystal in a stress-free state, and d0 = 0.0206 nm. 2dsinθ=λ Equation (1) ε=(d-d0) / d0Equation (2)
[0072] As shown in Fig. 9, the above-mentioned X-ray diffraction measurement was performed in each case where the angle (Ψ) between the normal to the main surface of the sample Sa and the normal to the crystal plane of the crystal Mb was 0°, 17°, 24°, 30°, 35°, 40°, and 45°, and the crystal lattice distortion ε at each angle (Ψ) was calculated. Then, the first internal stress σ Y and the second internal stress σ X sin 2 The relationship between Ψ and the crystal lattice distortion ε was plotted and the slope of the line was calculated using the following formula (3). The results are shown in Table 1. Note that in the internal stresses in Table 1, positive values indicate tensile stress, and negative values indicate compressive stress. In the side tilt method, the stress is measured in a direction at 90° to the beam direction, so the first internal stress σ Y and the second internal stress σ X When calculating, the sample was set so that the direction to be measured was perpendicular to the beam direction, and the measurements were performed. The results are shown in Tables 1 and 2. ε={(1+ν) / E}σsin 2 Ψ-(2ν / E)σ Equation (3)
[0073] In the above formula (3), E is the Young's modulus of the thermoelectric conversion material (130 GPa), and ν is the Poisson's ratio of the magnetic material (0.3). Detector D in FIG. 9 detects X-ray diffraction.
[0074] According to the above-mentioned X-ray diffraction measurement results, the thermoelectric conversion materials according to the respective examples had crystals with a body-centered cubic structure. FIG. 10 shows the XRD pattern of the thermoelectric conversion material according to Example 1.
[0075] As shown in Table 1, the coercive force of the thermoelectric conversion materials according to Examples 1 to 3, 5, and 6 was higher than that of the thermoelectric conversion material according to Comparative Example 1. As shown in Table 2, the coercive force of the thermoelectric conversion material according to Example 4 was higher than that of the thermoelectric conversion material according to Comparative Example 5. From these comparisons, it can be understood that in a thermoelectric conversion material exhibiting the Nernst effect including a magnetic alloy containing Fe, the thermoelectric conversion material is likely to have a high coercive force when the magnetic alloy further contains metal elements such as Ta, Nb, and W. The coercive force of the thermoelectric conversion materials according to Comparative Examples 2 to 4, in which the magnetic alloy contains Cr, Pt, or Zr, is lower than that of the thermoelectric conversion material according to Comparative Example 1. From the comparisons between Examples 1 to 3, 5, and 6 and Comparative Examples 2 to 4, it is considered important that in order to increase the coercive force of a thermoelectric conversion material, it contains a metal element that has a body-centered cubic lattice structure by itself and has an atomic radius of 132 picometers or more.
[0076] The coercive forces of the thermoelectric conversion materials of Examples 1 to 3, 5, and 6 were higher than that of the thermoelectric conversion material of Example 4. It can be understood that when the thickness of a thermoelectric conversion material is small, the coercive force of the thermoelectric conversion material tends to be high.
[0077] [Table 1]
[0078] [Table 2]
[0079] The first aspect of the present invention is A magnetic alloy containing Fe, a first metallic element, and a second metallic element, the first metal element and the second metal element are different metal elements other than Fe, the second metal element is a metal element having a body-centered cubic lattice structure by itself and an atomic radius of 132 picometers or more; exhibits the anomalous Nernst effect, A thermoelectric conversion material is provided.
[0080] A second aspect of the present invention is In the magnetic alloy, the content a of Fe based on the amount of substance, the content b of the first metal element based on the amount of substance, and the content c of the second metal element based on the amount of substance satisfy the conditions of 0.1≦b / (a+b)≦0.33 and 0.01≦c / (a+b+c)≦0.1; A thermoelectric conversion material according to a first aspect is provided.
[0081] A third aspect of the present invention is The magnetic alloy is Fe a D b E c The composition is In the composition, D is the first metallic element and E is the second metallic element; In the above composition, a, b, and c are rational numbers satisfying the condition a>b>c>0. The present invention provides a thermoelectric conversion material according to a first or second aspect.
[0082] A fourth aspect of the present invention is The magnetic alloy has a body-centered cubic lattice structure. The present invention provides a thermoelectric conversion material according to any one of the first to third aspects.
[0083] A fifth aspect of the present invention is The second metal element is at least one selected from the group consisting of Ta, Nb, and W; The present invention provides a thermoelectric conversion material according to any one of the first to fourth aspects.
[0084] A sixth aspect of the present invention is The first metal element includes at least one selected from the group consisting of Al, Si, Zn, Ga, Ge, Cd, In, and Sn, The present invention provides a thermoelectric conversion material according to any one of the first to fifth aspects.
[0085] A seventh aspect of the present invention is The thermoelectric conversion material has a thickness of 200 nm or less. The present invention provides a thermoelectric conversion material according to any one of the first to sixth aspects.
[0086] An eighth aspect of the present invention is The magnetic alloy is polycrystalline. The present invention provides a thermoelectric conversion material according to any one of the first to seventh aspects.
[0087] A ninth aspect of the present invention is The thermoelectric conversion material is in the form of a film, The internal stress σ of the film in a first direction along the plane of the film x and the internal stress σ of the film in a second direction perpendicular to the first direction and along the plane of the film. y Difference from |σ x -σ y | is 50MPa or more; The present invention provides a thermoelectric conversion material according to any one of the first to eighth aspects.
[0088] A tenth aspect of the present invention is The present invention provides a thermoelectric conversion element comprising a thermoelectric conversion material according to any one of the first to ninth aspects.
[0089] An eleventh aspect of the present invention is A thermometer including a thermoelectric conversion element according to a tenth aspect is provided.
[0090] A twelfth aspect of the present invention is A thermoelectric conversion element according to the tenth aspect of the present invention is provided. Detecting heat generated by storage batteries, A sensor is provided. [Explanation of symbols]
[0091] 1 Thermoelectric conversion materials 5 Thermoelectric conversion element
Claims
1. A magnetic alloy containing Fe, a first metal element, and a second metal element, the first metal element and the second metal element are different metal elements other than Fe, the second metal element is a metal element having a body-centered cubic lattice structure by itself and an atomic radius of 132 picometers or more; exhibits the anomalous Nernst effect, Thermoelectric conversion materials.
2. In the magnetic alloy, the content a of Fe based on the amount of substance, the content b of the first metal element based on the amount of substance, and the content c of the second metal element based on the amount of substance satisfy the conditions of 0.1≦b / (a+b)≦0.33 and 0.01≦c / (a+b+c)≦0.
1. The thermoelectric conversion material according to claim 1 .
3. The magnetic alloy is Fe a D b E c The composition is In the composition, D is the first metallic element and E is the second metallic element; In the composition, a, b, and c are rational numbers satisfying the condition a>b>c>0. The thermoelectric conversion material according to claim 1 .
4. The magnetic alloy has a body-centered cubic lattice structure. The thermoelectric conversion material according to claim 1 .
5. The second metal element is at least one selected from the group consisting of Ta, Nb, and W; The thermoelectric conversion material according to claim 1 .
6. The first metal element includes at least one selected from the group consisting of Al, Si, Zn, Ga, Ge, Cd, In, and Sn, The thermoelectric conversion material according to claim 1 .
7. The thermoelectric conversion material has a thickness of 200 nm or less. The thermoelectric conversion material according to claim 1 .
8. The magnetic alloy is polycrystalline. The thermoelectric conversion material according to claim 1 .
9. The thermoelectric conversion material is in the form of a film, The internal stress σ of the film in a first direction along the plane of the film x and the internal stress σ of the film in a second direction perpendicular to the first direction and along the plane of the film. y Difference from |σ x -σ y | is 50 MPa or more; The thermoelectric conversion material according to claim 1 .
10. A thermoelectric conversion element comprising the thermoelectric conversion material according to any one of claims 1 to 9.
11. A thermometer comprising the thermoelectric conversion element according to claim 10.
12. The thermoelectric conversion element according to claim 10, Detecting heat generated by storage batteries, Sensor.
Citation Information
Patent Citations
Thermoelectric conversion element and thermoelectric conversion device
WO2020218613A1